Suppose 2*n + 7*n = 27. Solve -2*o - n = 1 for o.
-2
Let w be 5*((-27)/(-15))/3. Suppose -w*z + 1 = -8. Suppose g + 4*t = -t + z, -t = 0. Solve -4 = g*x - 1 for x.
-1
Suppose -p = 2*p - 6. Suppose p*j = -5*z + 13 + 5, 12 = -2*z + 4*j. Solve -z*o + 4*o = -10 for o.
-5
Let n(m) = 1. Let h(t) = -t + 7. Let a(d) = h(d) - 5*n(d). Let y be a(2). Suppose -5*s = -y*s. Solve -2*r + s*r = 6 for r.
-3
Let m(n) be the third derivative of -n5⁄60 + 3*n4⁄8 + n3⁄3 - n2. Let h be m(9). Solve -3*q + 10 + h = 0 for q.
4
Let p = 8 - 4. Suppose -5*f + f + 284 = 0. Suppose -p*k + f = -9. Solve i = 6*i + k for i.
-4
Let j(d) be the second derivative of -d5⁄20 - 2*d4⁄3 + 3*d3⁄2 + d2 + 5*d. Let a be j(-9). Solve 1 = -a*l + 3 for l.
1
Let x = -139 - -213. Suppose -4*d = -x + 14. Solve -5*o = -d - 0 for o.
3
Let g(p) = -p**2 + 8*p. Let r = -34 - -50. Suppose -5*t + r = -24. Let n be g(t). Solve n = -3*b - b for b.
0
Let t = 28 + -2. Solve -5*f - t = -1 for f.
-5